Linking African Smallholders to High-Value Markets : Practitioner Perspectives on Benefits, Constraints, and Interventions - Henson, Spencer (Washington, DC: World Bank, 2012)
This paper provides the results of an international survey of practitioners with experience in facilitating the participation of African smallholder farmers in supply chains for higher-value and/or differentiated agricultural products. It explores their perceptions about the constraints inhibiting and the impacts associated with this supply chain participation. It also examines their perceptions about the factors affecting the success of project and policy interventions in this area, about how this success is and should be measured, and about the appropriate roles for national governments, the private sector, and development assistance entities in facilitating smallholder gains in this area. The results confirm a growing 'consensus' about institutional roles, yet suggest some ambiguity regarding the impacts of smallholder participation in higher-value supply chains and the appropriateness of the indicators most commonly used to gauge such impacts. The results also suggest a need to strengthen knowledge about both the 'old' and 'new' sets of constraints (and solutions) related to remunerative smallholder inclusion, in the form of the rising role of standards alongside more long-standing concerns about infrastructure and logistical links to markets.